2020
DOI: 10.3390/cells9071605
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 Trans-Signaling in the Brain Influences the Metabolic Phenotype of the 3xTg-AD Mouse Model of Alzheimer’s Disease

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder that causes the most prevalent dementia in the elderly people. Obesity and insulin resistance, which may cause major health problems per se, are risk factors for AD, and cytokines such as interleukin-6 (IL-6) have a role in these conditions. IL-6 can signal either through a membrane receptor or by trans-signaling, which can be inhibited by the soluble form of the co-receptor gp130 (sgp130). We have addressed the possibility that blocking IL-6 tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Additionally, as mentioned above, Escrig and colleagues also observed a lower body weight in GFAPsgp130 mice on a standard diet. Even if the lower body weight was not to a significant extent, this effect was also blunted after feeding an HFD [42]. In line with Escrig et al, food intake in male mice was not altered by centrally blocking IL-6tS.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Additionally, as mentioned above, Escrig and colleagues also observed a lower body weight in GFAPsgp130 mice on a standard diet. Even if the lower body weight was not to a significant extent, this effect was also blunted after feeding an HFD [42]. In line with Escrig et al, food intake in male mice was not altered by centrally blocking IL-6tS.…”
Section: Discussionsupporting
confidence: 79%
“…This is in accordance with findings by colleagues. Escrig et al revealed higher blood glucose levels in female GFAPsgp130 SD to SD mice, an effect that was also visible in male GFAPsgp130 mice [42]. This finding is supported by Timper et al, who revealed that central injection of IL-6 improved hepatic insulin action and glucose tolerance in obese mice [75].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In the context of aging, body weight also serves as a good indicator of the health status of the animal ( Barron et al, 2013 ). In the case of 3xTg-AD mice, we have shown that weight loss depends on intrinsic factors such as increased nocturnal activity ( Baeta-Corral et al, 2018b ) and hypermetabolic state ( Escrig et al, 2020 ) compared to age-matched NTg mice. We have also shown that weight loss is useful to monitor the aggravation of the AD-pathogenic processes ( Torres-Lista et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qing and colleagues demonstrate that after acute stress sympathetic nerves induce the increase in the levels of IL-6 which leads to other pathophysiologic effects [14]. It will be interesting to determine whether sympathetic nerves are also responsible for IL-6 increase in other pathological conditions, in which the role of this cytokine is well characterized, such as Alzheimer's disease [75][76][77], Asthma [78,79], atherosclerosis [80,81], inflammatory bowel disease [82,83], nephropathy [84], liver diseases [85], and others [38] (Fig. 2).…”
Section: Other Roles Of Il-6 Signalingmentioning
confidence: 99%